Feeding ecology of the giant otter (Pteronura brasiliensis) and the Neotropical otter (Lontra longicaudis) in Jaú National Park, Amazon, Brazil - Silva, Roberta Elise; Weber Rosas, Fernando Cesar; Zuanon, Jansen (Journal of Natural History, 2014)
This study compares the diets of the giant otter and the Neotropical otter, two Lutrinae species which feed mainly on fish. The study was carried out through the analyses of faecal samples collected between 2006 and 2008 (82 giant otter and 75 Neotropical otter) in the Jaú National Park. The giant otter feeds mainly on Cichlidae, Erythrinidae and Characidae, while the Neotropical otter consumes Doradidae, Loricariidae and Cichlidae. The two otter species had low diet similarity (Pianka's Index = 0.16). The giant otter consumed larger fish than the Neotropical otter, which probably explores shallow river parts in search of small catfish. Prey other than fish were more frequent in the diet of the Neotropical otter, whereas giant otters ate a greater diversity of fish families. Increasing knowledge of the feeding habits and interactions of these two top-order predators is vital to determine appropriate protection and management policies. © 2013 Taylor & Francis.
Keywords: Carnivore; Coexistence; Diet; Feeding; Feeding Ecology; Fish; Mammal; National Park; Protected Area; River; Amazonas; Jau National Park; Carnivora; Characidae; Cichlidae; Doradidae; Erythrinidae; Lontra Longicaudis; Loricariidae; Lutrinae; Pteronura Brasiliensis